University Paradiplomacy: The internationalization of higher education in Latin America - García Waldman, David Horacio; Jiménez Quintana, Paulina; Zapata Morán, María Gabriela (Universidad Autónoma de Nuevo León, 2018)
This article is the product of a literature review, which objective is to analyze the impact that universities have as agents of Paradiplomacy in the international sphere through their internationalization processes and strategies for which the case of some Universities of three Latin American countries, Chile, Argentina and Brazil were taken. The method of analysis was applied, with a qualitative approach, non-experimental design, under a transversal documentary-bibliographic level. After the documentary review, a brief analysis is carried out in which different internationalization strategies were found, as well as the historical processes that caused the Universities to expand. It is concluded that the internationalization of higher education in Latin America continues to face challenges, however, the strategies implemented by these countries have launched their universities to the international market.